“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Coherent driving of direct and indirect excitons in a quantum dot molecule - Bopp, Frederik; Schall, Johannes; Bart, Nikolai; Vögl, Florian; Cullip, Charlotte; Sbresny, Friedrich; Boos, Katarina; Thalacker, Christopher; Lienhart, Michelle; Rodt, Sven; Reuter, Dirk; Ludwig, Arne; et al. (Physical Review B)

Single-shot spatial instability and electric control of polariton condensates at room temperature - Gao, Ying; Ma, Xuekai; Zhai, Xiaokun; Xing, Chunzi; Gao, Meini; Dai, Haitao; Wu, Hao; Liu, Tong; Ren, Yuan; Wang, Xiao; Pan, Anlian; Hu, Wei; et al. (Physical Review B)

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Structural fingerprints in the reflectance anisotropy of AlInP(001) - Ruiz Alvarado, Isaac Azahel; Zare Pour, Mohammad Amin; Hannappel, Thomas; Schmidt, Wolf Gero (Physical Review B)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

Pulse shaping for on-demand emission of single Raman photons from a quantum-dot biexciton - Praschan, Tom; Heinze, Dirk; Breddermann, Dominik; Zrenner, Artur; Walther, Andrea; Schumacher, Stefan (Physical Review B)

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

Second-harmonic generation in atomically thin 1T−TiSe2 and its possible origin from charge density wave transitions - Zhang, Ruiming; Ruan, Wei; Yu, Junyao; Gao, Libo; Berger, Helmuth; Forró, László; Watanabe, Kenji; Taniguchi, Takashi; Ranjbar, Ahmad; Belosludov, Rodion V.; Kühne, Thomas; Bahramy, Mohammad Saeed; et al. (Physical Review B)

CENT2: Improved charge equilibration via neural network technique - Khajehpasha, Ehsan Rahmatizad; Finkler, Jonas A.; Kühne, Thomas; Ghasemi, Alireza (Physical Review B)

Multiple Rabi rotations of trions in InGaAs quantum dots observed by photon echo spectroscopy with spatially shaped laser pulses - Grisard, S.; Rose, Hendrik; Trifonov, A. V.; Reichhardt, R.; Reiter, D. E.; Reichelt, Matthias; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M.; Meier, Torsten; Akimov, I. A. (Physical Review B)

Coherent contributions to population dynamics in a semiconductor microcavity - Paul, J.; Rose, Hendrik; Swagel, E.; Meier, Torsten; Wahlstrand, J. K.; Bristow, A. D. (Physical Review B)

Pulse shaping for on-demand emission of single Raman photons from a quantum-dot biexciton - Praschan, Tom; Heinze, Dirk; Breddermann, Dominik; Zrenner, Artur; Walther, Andrea; Schumacher, Stefan (Physical Review B)

Tuning domain wall conductivity in bulk lithium niobate by uniaxial stress - Singh, Ekta; Beccard, Henrik; Amber, Zeeshan H.; Ratzenberger, Julius; Hicks, Clifford W.; Rüsing, Michael; Eng, Lukas M. (Physical Review B)
Conductive domain walls (DWs) in insulating ferroelectrics have recently attracted considerable attention due to their unique topological, optical, and electronic properties, and offer potential applications such as in memory devices or rewritable circuitry. The electronic properties of DWs can be tuned by the application of strain, hence controlling the charge carrier density at DWs. In this paper, we study the influence of uniaxial stress on the conductivity of DWs in the bulk single crystal lithium niobate (LiNbO3). Using conductive atomic force microscopy, we observe a large asymmetry in the conductivity of DWs, where only negatively screened walls, so called head-to-head DWs, are becoming increasingly conductive, while positively screened, tail-to-tails DWs, show a decrease in conductivity. This asymmetry of DW conductivity agrees with our theoretical model based on the piezoelectric effect. In addition, we observed that the current in the DW increases up to an order of magnitude for smaller compressive stresses of 100 MPa. This response of DWs remained intact for multiple stress cycles over two months, opening a path for future applications.

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

Electronic structure of the Si(111)3×3R30°−B surface from theory and photoemission spectroscopy - Aldahhak, Hazem; Hogan, Conor; Lindner, Susi; Appelfeller, Stephan; Eisele, Holger; Schmidt, Wolf Gero; Dähne, Mario; Gerstmann, Uwe; Franz, Martin (Physical Review B)

Second harmonic generation on excitons in ZnO/(Zn,Mg)O quantum wells with built-in electric fields - Mund, Johannes; Yakovlev, Dmitri R.; Sadofev, Sergey; Meier, Cedrik; Bayer, Manfred (Physical Review B)

Microscopic analysis of high harmonic generation in semiconductors with degenerate bands - Thong, Le Huu; Ngo, Cong; Duc, Huynh Thanh; Song, Xiaohong; Meier, Torsten (Physical Review B)

Hyperfine and nuclear quadrupole splitting of the NV− ground state in 4H-SiC - Murzakhanov, F. F.; Yavkin, B. V.; Mamin, G. V.; Orlinskii, S. B.; von Bardeleben, H. J.; Biktagirov, Timur; Gerstmann, Uwe; Soltamov, V. A. (Physical Review B)

Electronic structure of the Si(111)3×3R30∘−B surface from theory and photoemission spectroscopy - Aldahhak, Hazem; Hogan, Conor; Lindner, Susi; Appelfeller, Stephan; Eisele, Holger; Schmidt, Wolf Gero; Dähne, Mario; Gerstmann, Uwe; Franz, Martin (Physical Review B)

Impact of screening and relaxation on weakly coupled two-dimensional heterostructures - Nguyen, T. T. Nhung; Sollfrank, T.; Tegenkamp, C.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Surface localized phonon modes at the Si(553)-Au nanowire system - Plaickner, Julian; Speiser, Eugen; Braun, Christian; Schmidt, Wolf Gero; Esser, Norbert; Sanna, Simone (Physical Review B)

Erratum: Efficient implementation of the GW approximation within the all-electron FLAPW method [Phys. Rev. B 81, 125102 (2010)] - Friedrich, Christoph; Blügel, Stefan; Schindlmayr, Arno (Physical Review B)

Ultrafast electric control of cavity mediated single-photon and photon-pair generation with semiconductor quantum dots - Bauch, David; Heinze, Dirk Florian; Förstner, Jens; Jöns, Klaus; Schumacher, Stefan (Physical Review B)
Employing the ultrafast control of electronic states of a semiconductor quantum dot in a cavity, we introduce an approach to achieve on-demand emission of single photons with almost perfect indistinguishability and photon pairs with near ideal entanglement. Our scheme is based on optical excitation off resonant to a cavity mode followed by ultrafast control of the electronic states using the time-dependent quantum-confined Stark effect, which then allows for cavity-resonant emission. Our theoretical analysis considers cavity-loss mechanisms, the Stark effect, and phonon-induced dephasing, allowing realistic predictions for finite temperatures.
Keywords: tet_topic_qd

Structuring coflowing and counterflowing currents of polariton condensates in concentric ring-shaped and elliptical potentials - Barkhausen, Franziska; Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

Polaronic enhancement of second-harmonic generation in lithium niobate - Kozub, Agnieszka L.; Schindlmayr, Arno; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review B)
Density-functional theory within a Berry-phase formulation of the dynamical polarization is used to determine the second-order susceptibility χ(2) of lithium niobate (LiNbO3). Defect trapped polarons and bipolarons are found to strongly enhance the nonlinear susceptibility of the material, in particular if localized at NbV–VLi defect pairs. This is essentially a consequence of the polaronic excitation resulting in relaxation-induced gap states. The occupation of these levels leads to strongly enhanced χ(2) coefficients and allows for the spatial and transient modification of the second-harmonic generation of macroscopic samples.

Nondegenerate two-photon absorption in ZnSe: Experiment and theory - Krauss-Kodytek, L.; Hannes, W.-R.; Meier, Torsten; Ruppert, C.; Betz, M. (Physical Review B)

Nondegenerate two-photon absorption in ZnSe: Experiment and theory - Krauss-Kodytek, L.; Hannes, Wolf-Rüdiger; Meier, Torsten; Ruppert, C.; Betz, M. (Physical Review B)

Broadband coherent anti-Stokes Raman scattering for crystalline materials - Hempel, Franz; Reitzig, Sven; Rüsing, Michael; Eng, Lukas M. (Physical Review B)
Broadband coherent anti-Stokes Raman scattering (B-CARS) has emerged in recent years as a promising chemosensitive high-speed imaging technique. B-CARS allows for the detection of vibrational sample properties in analogy to spontaneous Raman spectroscopy, but also makes electronic sample environments accessible due to its resonant excitation mechanism. Nevertheless, this technique has only gained interest in the biomedical field so far, whereas CARS investigations on solid-state materials are rare and concentrate on layered, two-dimensional materials such as graphene and hexagonal boron nitride . In this work, we discuss the specific properties of this technique when applied to single-crystalline samples, with respect to signal generation, phase matching, and selection rules in the model systems lithium niobate and lithium tantalate. Via polarized B-CARS measurements and subsequent phase retrieval, we validate the predicted selection rules, unequivocally assign the phonons of the A1(TO), E(TO) and A1(LO) branches to the detected CARS peaks, and address differences in spontaneous Raman spectroscopy concerning peak frequencies and scattering efficiencies. We thus establish this technique for future investigations of solid-state materials, specifically in the field of ferroelectric single crystals.

Hybrid density functional theory benchmark study on lithium manganese oxides - Eckhoff, Marco; Blöchl, Peter E.; Behler, Jörg (Physical Review B)
Keywords: pc2-ressources

Electrostatic potential shape of gate-defined quantum point contacts - Geier, M.; Freudenfeld, J.; Silva, J. T.; Umansky, V.; Reuter, Dirk; Wieck, A. D.; Brouwer, P. W.; Ludwig, S. (Physical Review B)

Electrical detection of excitonic states by time-resolved conductance measurements - Ebler, C.; Labud, P. A.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Ludwig, A. (Physical Review B)

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Spin splitting in a MoS2 monolayer induced by exciton interaction - Li, Yao; Li, Guangyao; Zhai, Xiaokun; Xiong, Shifu; Liu, Hongjun; Wang, Xiao; Chen, Haitao; Gao, Ying; Zhang, Xiu; Liu, Tong; Ren, Yuan; Ma, Xuekai; et al. (Physical Review B)

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Carbon vacancy-related centers in 3C-silicon carbide: Negative-U properties and structural transformation - von Bardeleben, H. J.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Unconventional phase III of high-pressure solid hydrogen - Azadi, Sam; Kühne, Thomas D. (Physical Review B)

Random network models with variable disorder of geometry - Klümper, A.; Nuding, W.; Sedrakyan, A. (Physical Review B)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Excited-state band mapping and momentum-resolved ultrafast population dynamics in In/Si(111) nanowires investigated with XUV-based time- and angle-resolved photoemission spectroscopy - Nicholson, C. W.; Puppin, M.; Lücke, A.; Gerstmann, Uwe; Krenz, Marvin; Schmidt, Wolf Gero; Rettig, L.; Ernstorfer, R.; Wolf, M. (Physical Review B)

Higher-order contributions and nonperturbative effects in the nondegenerate nonlinear optical absorption of semiconductors using a two-band model - Hannes, Wolf-Rüdiger; Meier, Torsten (Physical Review B)

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Ballistic photocurrents in semiconductor quantum wells caused by the excitation of asymmetric excitons - Duc, Huynh Thanh; Ngo, Cong; Meier, Torsten (Physical Review B)

Decay and revival of electron spin polarization in an ensemble of (In,Ga)As quantum dots - Evers, E.; Belykh, V. V.; Kopteva, N. E.; Yugova, I. A.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Spin inertia of resident and photoexcited carriers in singly charged quantum dots - Zhukov, E. A.; Kirstein, E.; Smirnov, D. S.; Yakovlev, D. R.; Glazov, M. M.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Greilich, A. (Physical Review B)

Theory of spin inertia in singly charged quantum dots - Smirnov, D. S.; Zhukov, E. A.; Kirstein, E.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Greilich, A.; Glazov, M. M. (Physical Review B)

Probing quasi-one-dimensional band structures by plasmon spectroscopy - Lichtenstein, T.; Mamiyev, Z.; Braun, C.; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C.; Pfnür, H. (Physical Review B)

Calculation of spin-spin zero-field splitting within periodic boundary conditions: Towards all-electron accuracy - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review B)

Vibrational properties of the Au-(3×3)/Si(111) surface reconstruction - Halbig, B.; Liebhaber, M.; Bass, U.; Geurts, J.; Speiser, E.; Räthel, J.; Chandola, S.; Esser, N.; Krenz, Marvin; Neufeld, Sergej; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

Probing quasi-one-dimensional band structures by plasmon spectroscopy - Lichtenstein, T.; Mamiyev, Z.; Braun, Christian; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C.; Pfnür, H. (Physical Review B)

Microscopic theory of cavity-enhanced single-photon emission from optical two-photon Raman processes - Breddermann, Dominik; Praschan, Tom; Heinze, Dirk Florian; Binder, Rolf; Schumacher, Stefan (Physical Review B)

Polytypism driven zero-field splitting of silicon vacancies in 6H-SiC - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe; Yavkin, Boris; Orlinskii, Sergei; Baranov, Pavel; Dyakonov, Vladimir; Soltamov, Victor (Physical Review B)

Spin pairing versus spin chains at Si(553)-Au surfaces - Braun, Christian; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review B)

Metal-insulator transition in the dimerized organic conductor κ−(BEDT-TTF)2Hg(SCN)2Br - Ivek, Tomislav; Beyer, Rebecca; Badalov, Sabuhi; Čulo, Matija; Tomić, Silvia; Schlueter, John A.; Zhilyaeva, Elena I.; Lyubovskaya, Rimma N.; Dressel, Martin (Physical Review B)

Spin dynamics of quadrupole nuclei in InGaAs quantum dots - Kuznetsova, M. S.; Cherbunin, R. V.; Gerlovin, I. Ya.; Ignatiev, I. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Photon echoes from (In,Ga)As quantum dots embedded in a Tamm-plasmon microcavity - Salewski, M.; Poltavtsev, S. V.; Kapitonov, Yu. V.; Vondran, J.; Yakovlev, D. R.; Schneider, C.; Kamp, M.; Höfling, S.; Oulton, R.; Akimov, I. A.; Kavokin, A. V.; Bayer, M. (Physical Review B)
We report on the coherent optical response from an ensemble of (In,Ga)As quantum dots (QDs) embedded in a planar Tamm-plasmon microcavity with a quality factor of approximately 100. Significant enhancement of the light-matter interaction is demonstrated under selective laser excitation of those quantum dots which are in resonance with the cavity mode. The enhancement is manifested through Rabi oscillations of the photon echo, demonstrating coherent control of excitons with picosecond pulses at intensity levels more than an order of magnitude smaller as compared with bare quantum dots. The decay of the photon echo transients is weakly changed by the resonator, indicating a small decrease of the coherence time T2 which we attribute to the interaction with the electron plasma in the metal layer located close (40 nm) to the QD layer. Simultaneously we see a reduction of the population lifetime T1, inferred from the stimulated photon echo, due to an enhancement of the spontaneous emission by a factor of 2, which is attributed to the Purcell effect, while nonradiative processes are negligible, as confirmed from time-resolved photoluminescence.

Double resonant plasmonic nanoantennas for efficient second harmonic generation in zinc oxide - Weber, Nils; Protte, Maximilian; Walter, Felicitas; Georgi, Philip; Zentgraf, Thomas; Meier, Cedrik (Physical Review B)

Solving the Bethe-Salpeter equation for the second-harmonic generation in Zn chalcogenides - Riefer, A.; Schmidt, Wolf Gero (Physical Review B)

Understanding band alignments in semiconductor heterostructures: Composition dependence and type-I–type-II transition of natural band offsets in nonpolar zinc-blendeAlxGa1−xN/AlyGa1−yNcomposites - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (Physical Review B)

Electron paramagnetic resonance calculations for hydrogenated Si surfaces - Rohrmüller, M.; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review B)

Tuning the conductivity along atomic chains by selective chemisorption - Edler, F.; Miccoli, I.; Stöckmann, J. P.; Pfnür, H.; Braun, Christian; Neufeld, Sergej; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

Understanding band alignments in semiconductor heterostructures: Composition dependence and type-I–type-II transition of natural band offsets in nonpolar zinc-blendeAlxGa1−xN/AlyGa1−yNcomposites - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (Physical Review B)

Vortex-vortex control in exciton-polariton condensates - Ma, Xuekai; Schumacher, Stefan (Physical Review B)

Anisotropic excitons and their contributions to shift current transients in bulk GaAs - Podzimski, Reinold; Duc, Huynh Thanh; Meier, Torsten (Physical Review B)

Time-resolved photon echoes from donor-bound excitons in ZnO epitaxial layers - Poltavtsev, S. V.; Kosarev, A. N.; Akimov, I. A.; Yakovlev, D. R.; Sadofev, S.; Puls, J.; Hoffmann, S. P.; Albert, M.; Meier, Cedrik; Meier, Torsten; Bayer, M. (Physical Review B)

Damping of Rabi oscillations in intensity-dependent photon echoes from exciton complexes in a CdTe/(Cd,Mg)Te single quantum well - Poltavtsev, S. V.; Reichelt, Matthias; Akimov, I. A.; Karczewski, G.; Wiater, M.; Wojtowicz, T.; Yakovlev, D. R.; Meier, Torsten; Bayer, M. (Physical Review B)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

All-optical tailoring of single-photon spectra in a quantum-dot microcavity system - Breddermann, D.; Heinze, Dirk Florian; Binder, R.; Zrenner, Artur; Schumacher, Stefan (Physical Review B)

Electron spin dynamics in cubic GaN - Buß, J. H.; Schupp, T.; As, Donat Josef; Brandt, O.; Hägele, D.; Rudolph, J. (Physical Review B)

Stabilizing nuclear spins around semiconductor electrons via the interplay of optical coherent population trapping and dynamic nuclear polarization - Onur, A. R.; de Jong, J. P.; O'Shea, D.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Physical Review B)

Reconstruction of nuclear quadrupole interaction in (In,Ga)As/GaAs quantum dots observed by transmission electron microscopy - Sokolov, P. S.; Petrov, M. Yu.; Mehrtens, T.; Müller-Caspary, K.; Rosenauer, A.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

All-optical tailoring of single-photon spectra in a quantum-dot microcavity system - Breddermann, D.; Heinze, D.; Binder, R.; Zrenner, Artur; Schumacher, Stefan (Physical Review B)
Semiconductor quantum-dot cavity systems are promising sources for solid-state-based on-demand generation of single photons for quantum communication. Commonly, the spectral characteristics of the emitted single photon are fixed by system properties such as electronic transition energies and spectral properties of the cavity. In the present work we study cavity-enhanced single-photon generation from the quantum-dot biexciton through a partly stimulated nondegenerate two-photon emission. We show that frequency and linewidth of the single photon can be fully controlled by the stimulating laser pulse, ultimately allowing for efficient all-optical spectral shaping of the single photon.

Existence of topological nontrivial surface states in strained transition metals: W, Ta, Mo, and Nb - Thonig, Danny; Rauch, Tomáš; Mirhosseini, Hossein; Henk, Jürgen; Mertig, Ingrid; Wortelen, Henry; Engelkamp, Bernd; Schmidt, Anke B.; Donath, Markus (Physical Review B)

Orbital-symmetry-selective spin characterization of Dirac-cone-like state on W(110) - Miyamoto, K.; Wortelen, H.; Mirhosseini, Hossein; Okuda, T.; Kimura, A.; Iwasawa, H.; Shimada, K.; Henk, J.; Donath, M. (Physical Review B)

Experimental realization of a polariton beam amplifier - Niemietz, Dominik; Schmutzler, Johannes; Lewandowski, Przemyslaw; Winkler, Karol; Aßmann, Marc; Schumacher, Stefan; Brodbeck, Sebastian; Kamp, Martin; Schneider, Christian; Höfling, Sven; Bayer, Manfred (Physical Review B)

Dynamics of exciton-polaritons in discrete lattices under incoherent localized pumping - Yulin, A. V.; Chestnov, I. Yu.; Ma, X.; Schumacher, Stefan; Peschel, U.; Egorov, O. A. (Physical Review B)

Polarization dependence of nonlinear wave mixing of spinor polaritons in semiconductor microcavities - Lewandowski, Przemyslaw; Lafont, Ombline; Baudin, Emmanuel; Chan, Chris K. P.; Leung, P. T.; Luk, Samuel M. H.; Galopin, Elisabeth; Lemaître, Aristide; Bloch, Jacqueline; Tignon, Jerome; Roussignol, Philippe; Kwong, N. H.; et al. (Physical Review B)

Vibration eigenmodes of the Au-(5×2)/Si(111) surface studied by Raman spectroscopy and first-principles calculations - Liebhaber, M.; Halbig, B.; Bass, U.; Geurts, J.; Neufeld, Sergej; Sanna, S.; Schmidt, Wolf Gero; Speiser, E.; Räthel, J.; Chandola, S.; Esser, N. (Physical Review B)

LiNbO3 electronic structure: Many-body interactions, spin-orbit coupling, and thermal effects - Riefer, Arthur; Friedrich, Michael; Sanna, Simone; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Physical Review B)
The influence of electronic many-body interactions, spin-orbit coupling, and thermal lattice vibrations on the electronic structure of lithium niobate is calculated from first principles. Self-energy calculations in the GW approximation show that the inclusion of self-consistency in the Green function G and the screened Coulomb potential W opens the band gap far stronger than found in previous G0W0 calculations but slightly overestimates its actual value due to the neglect of excitonic effects in W. A realistic frozen-lattice band gap of about 5.9 eV is obtained by combining hybrid density functional theory with the QSGW0 scheme. The renormalization of the band gap due to electron-phonon coupling, derived here using molecular dynamics as well as density functional perturbation theory, reduces this value by about 0.5 eV at room temperature. Spin-orbit coupling does not noticeably modify the fundamental gap but gives rise to a Rashba-like spin texture in the conduction band.

Strain-induced quasi-one-dimensional rare-earth silicide structures on Si(111) - Timmer, F.; Oelke, R.; Dues, C.; Sanna, S.; Schmidt, Wolf Gero; Franz, M.; Appelfeller, S.; Dähne, M.; Wollschläger, J. (Physical Review B)

Surface vibrational Raman modes of In:Si(111)(4×1)and(8×2)nanowires - Speiser, E.; Esser, N.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Grand canonical Peierls transition in In/Si(111) - Jeckelmann, Eric; Sanna, Simone; Schmidt, Wolf Gero; Speiser, Eugen; Esser, Norbert (Physical Review B)

Rare-earth silicide thin films on the Si(111) surface - Sanna, S.; Dues, C.; Schmidt, Wolf Gero; Timmer, F.; Wollschläger, J.; Franz, M.; Appelfeller, S.; Dähne, M. (Physical Review B)

Atomic size effects studied by transport in single silicide nanowires - Miccoli, I.; Edler, F.; Pfnür, H.; Appelfeller, S.; Dähne, M.; Holtgrewe, K.; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

Collective state transitions of exciton-polaritons loaded into a periodic potential - Winkler, K.; Egorov, O. A.; Savenko, I. G.; Ma, Xuekai; Estrecho, E.; Gao, T.; Müller, S.; Kamp, M.; Liew, T. C. H.; Ostrovskaya, E. A.; Höfling, S.; Schneider, C. (Physical Review B)

Dynamics of exciton-polaritons in discrete lattices under incoherent localized pumping - Yulin, A. V.; Chestnov, I. Yu.; Ma, Xuekai; Schumacher, S.; Peschel, U.; Egorov, O. A. (Physical Review B)

Incoherent control of topological charges in nonequilibrium polariton condensates - Ma, Xuekai; Peschel, Ulf; Egorov, Oleg A. (Physical Review B)

Ultrafast shift and rectification photocurrents in GaAs quantum wells: Excitation intensity dependence and the importance of band mixing - Duc, Huynh Thanh; Podzimski, Reinold; Priyadarshi, Shekhar; Bieler, Mark; Meier, Torsten (Physical Review B)
A microscopic approach that is based on the multisubband semiconductor Bloch equations formulated in the basis of a 14-band k⋅p model is employed to compute the temporal dynamics of photocurrents in GaAs quantum wells following excitation with femtosecond laser pulses. This approach provides a transparent description of the interband, intersubband, and intraband excitations, fully includes all resonant as well as off-resonant excitations, and treats the light-matter interaction nonperturbatively. For linearly polarized excitations, the photocurrents contain contributions from shift and rectification currents. We numerically compute and analyze these currents generated by excitation with femtosecond laser pulses for [110]- and [111]-oriented GaAs quantum wells. It is shown that the often employed perturbative χ(2) approach breaks down for peak fields larger than about 10 kV/cm, and that nonperturbative effects lead to a reduction of the peak values of the shift and rectification currents and to temporal oscillations that originate from Rabi flopping. In particular, we find a complex oscillatory photon energy dependence of the magnitudes of the shift and rectification currents. Our simulations demonstrate that this dependence is the result of mixing between the heavy- and light-hole valence bands. This is a surprising finding since the band mixing has an even larger influence on the strength of the photocurrents than the absorption coefficient. For [110]-oriented GaAs quantum wells, the calculated photon energy dependence is compared to experimental results, and good agreement is obtained. This validates our theoretical approach.

Ultrafast dynamical response of the lower exciton-polariton branch in CdZnTe - Lohrenz, J.; Melzer, S.; Ruppert, C.; Akimov, I. A.; Mariette, H.; Reichelt, Matthias; Trautmann, Alexander; Meier, Torsten; Betz, M. (Physical Review B)
We investigate the transient optical response in high-quality Cd0.88Zn0.12Te crystals in the regime of slow light propagation on the lower exciton-polariton branch. Femtosecond photoexcitation leads to very substantial transmission changes in a ∼10-meV broad spectral range within the transparency window of the unexcited semiconductor. These nonlinear optical signatures decay on picosecond time scales governed by carrier thermalization and recombination. The temporal and spectral dependence indicate the dynamical optical response as arising from excitation-induced dephasing and perturbed free induction decay. Model simulations for the optical response taking into account the actual exciton-polariton dispersion and excitation-induced dephasing of a nonlinearly driven two-level system support this interpretation.

Vibrational properties of LiNb1−xTaxO3 mixed crystals - Rüsing, Michael; Sanna, Simone; Neufeld, Sergej; Berth, Gerhard; Schmidt, Wolf Gero; Zrenner, Artur; Yu, H.; Wang, Y.; Zhang, H. (Physical Review B)
Congruent lithium niobate and lithium tantalate mixed crystals have been grown over the complete compositional range with the Czochralski method. The structural and vibrational properties of the mixed crystals are studied extensively by x-ray diffraction measurements, Raman spectroscopy, and density functional theory. The measured lattice parameters and vibrational frequencies are in good agreement with our theoretical predictions. The observed dependence of the Raman frequencies on the crystal composition is discussed on the basis of the calculated phonon displacement patterns. The phononic contribution to the static dielectric tensor is calculated by means of the generalized Lyddane-Sachs-Teller relation. Due to the pronounced dependence of the optical response on the Ta concentration, lithium niobate tantalate mixed crystals represent a perfect model system to study the properties of uniaxial mixed ferroelectric materials for application in integrated optics.

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)